2022
DOI: 10.3390/nano12030306
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Morphology and Composition of Laser-Induced Periodic Structures on Titanium Films with Femtosecond Laser Wavelength and Ambient Environment

Abstract: Recently, highly uniform thermochemical laser-induced periodic surface structures (TLIPSS) have attracted significant research attention due to their practical applicability for upscalable fabrication of periodic surface morphologies important for surface functionalization, diffraction optics, sensors, etc. When processed by femtosecond (fs) laser pulses in oxygen-containing environments, TLIPSS are formed on the material surface as parallel protrusions upon local oxidation in the maxima of the periodic intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Studies have shown that laser peak fluence, the number of laser pulses, laser polari zation state, pulse duration, and the processing environment are all key parameters af fecting LIPSS [47][48][49][50][51][52].…”
Section: Laser Parameters That Control Lipssmentioning
confidence: 99%
“…Studies have shown that laser peak fluence, the number of laser pulses, laser polari zation state, pulse duration, and the processing environment are all key parameters af fecting LIPSS [47][48][49][50][51][52].…”
Section: Laser Parameters That Control Lipssmentioning
confidence: 99%
“…However, laser processing at the nanometer scale is developing very rapidly [ 1 ]. Some examples of nanoscale laser processing include laser nanolithography [ 2 ], laser ablation for nanoparticle synthesis [ 3 ], and laser-induced surface modifications [ 4 , 5 , 6 ]. Among these techniques, laser-induced surface modifications offer precise control over surface relief and phase composition, thereby influencing a wide range of properties such as wettability, antimicrobial characteristics, and tribology.…”
Section: Introductionmentioning
confidence: 99%
“…Our Special Issue attracted high-quality contributions from both academics and from industry and finally bundles together 1 review paper of Jürgen Reif [ 3 ], 1 perspective article [ 4 ], and 17 original research articles [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. These publications are focusing on the latest achievements in areas of laser–matter interaction [ 16 , 18 , 22 , 23 , 27 , 30 , 31 ], nonlinear optics and photonics [ 22 , 23 , 26 ], spatial beam shaping [ 15 , 28 ], surface dynamics [ 4 , 17 , 22 , 23 ], micro- and nanotechnology [ 16 , 18 , 20 , 24 , 26 , 27 , 31 ], laser-induced periodic surface structures (LIPSS) [ 3 , 4 , 19 , 20 , 21 , 27 ,…”
mentioning
confidence: 99%